1992
DOI: 10.1002/bjs.1800790222
|View full text |Cite
|
Sign up to set email alerts
|

Oesophagitis and pH of refluxate: an experimental and clinical study

Abstract: This experimental and clinical study examined the relationship between oesophageal damage and optimal pH of refluxate, and whether 24-h pH monitoring at optimal pH could discriminate the severity of oesophagitis. The rabbit oesophagus was perfused in vivo with pepsin and hydrochloric acid solutions of differing pH for 60 min. Maximal oesophageal damage coincided with peptic solutions at pH 1.5-2.5. Fifty-nine patients with proven gastro-oesophageal reflux disorders were tested for manometric features of the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…On the one hand, gastric acid may play a role in the pathogenesis of gastroesophageal reflux disease (46,47). Both increased basal and food-stimulated acid secretion likely contribute to longer duration of esophageal acid exposure (5)(6)(7)48).…”
Section: Time (Min)mentioning
confidence: 99%
“…On the one hand, gastric acid may play a role in the pathogenesis of gastroesophageal reflux disease (46,47). Both increased basal and food-stimulated acid secretion likely contribute to longer duration of esophageal acid exposure (5)(6)(7)48).…”
Section: Time (Min)mentioning
confidence: 99%
“…Pepsin solutions above pH 2.3 did not cause mucosal injury in this study, reflecting the in vitro activation of porcine pepsin at a pH below 2.5. Similar results were reported by Zaninotto et al, who observed mucosal erosions in rabbit oesopha gus perfused with pepsin solutions at pH 1.5 and 2.0. but not when solutions of pH 3.0 or 4.0 were used [6]. Bile salts may also increase the injurious effects of acid by increasing the permeability of the oesophageal mucosa to hydrogen ions |7|.…”
Section: The Injurious Action Of Acidmentioning
confidence: 99%
“…The pH dependency of oesophageal mucosal injury has been demonstrated in vari ous animal models [5,6]. Goldberg et al showed that perfusion of the feline oesophagus over a 1-hour period with hydrochloric acid produced oesophagitis only when solutions of pH equal to or less than 1.3 were utilized [5].…”
Section: The Injurious Action Of Acidmentioning
confidence: 99%
“…Eine Überproduktion an Ma gensäure findet sich aber selten: mehr als 90% aller Refluxpatien ten sind normazid [33]. Patienten mit schwerer Refluxösophagitis haben als Gruppe niedrigere pH-Werte im Ösophagus als jene Pa tienten mit milder Refluxösophagitis [34]. Allerdings besteht keine strenge Korrelation zwischen dem Schweregrad der Erkrankung und pH-metrischen Daten [34|.…”
Section: öSophagusperistaltik Und Clearancefunktionunclassified